2010
DOI: 10.1002/jobm.201000074
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of Borrelia burgdorferi organisms – RNA, lipid and protein composition in context with the spirochetes' shape

Abstract: Borrelia burgdorferi, the agent of Lyme borreliosis, has the ability to undergo morphological transformation from a motile spirochetal to non-motile spherical shape when it encounters unfavorable conditions. However, little information is available on the mechanism that enables the bacterium to change its shape and whether major components of the cells--nucleic acids, proteins, lipids--are possibly modified during the process. Deducing from investigations utilizing electron microscopy, it seems that shape alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…The change in phenotypic expression could also lead to structural alterations in the spirochete form and induction of the cyst form, a knob-shaped structure containing one or multiple spirochetes 2124. Cysts have a low metabolic rate that enables them to survive in a hostile environment until conditions become favorable for them to multiply again 2125.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in phenotypic expression could also lead to structural alterations in the spirochete form and induction of the cyst form, a knob-shaped structure containing one or multiple spirochetes 2124. Cysts have a low metabolic rate that enables them to survive in a hostile environment until conditions become favorable for them to multiply again 2125.…”
Section: Discussionmentioning
confidence: 99%
“…Both cysts and granules are together referred to as round body forms in this study. Several studies have shown that B. burgdorferi can convert from the spirochete form to the round body form in vitro when presented with an unfavorable environment, and the organism can revert back to the spirochete form when conditions are again favorable for growth 2124. The presence of atypical forms of B. burgdorferi may be the reason why the spirochete can survive in infected tissues for years or even for decades 2124…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Figure 4, the most commonly published method of inducing round RB forms of Borrelia spp. is through osmotic shock via exposure to distilled water [313,314,321,[327][328][329]. Water shock is also consistently reported to be the fastest for the conversion of large proportions of spirochetes into round bodies (Table A1).…”
Section: Pleomorphymentioning
confidence: 99%
“…are not only inducible in vitro, but they have also been detected within the enzootic life cycle of the spirochete, specifically within the midgut of the tick vector [336]. These forms have been loosely described as spherules, granules, gemmae, cysts, coccoid forms, and round bodies at different points throughout the literature (Table 4; [270,313,314,328,329,333,334,337]). Likewise, a wide variety of methods have been used to generate and evaluate these forms, and yet the resulting morphotypes are treated synonymously (Table A1).…”
Section: Pleomorphymentioning
confidence: 99%
“…Immune evasion via alterations in its physical structure may also contribute to Bbsl survival. Such alterations include phasic and antigenic variations [149][150][151][152][153], producing changes in the expression of outer surface proteins (Osp), and morphologic changes leading to cell-wall deficient forms, round bodies, spherocytes and "cyst" forms [154][155][156][157][158][159].…”
Section: Pathophysiologic Basis Of Chronic Lyme Diseasementioning
confidence: 99%